Low-intensity swimming with blood flow restriction over 5 weeks increases VO2peak: A randomized controlled trial using Bayesian informative prior distribution - Held, S.; Rappelt, L.; Deutsch, J.-P.; Rein, R.; Wiedenmann, T.; Schiffer, A.; Bieder, A.; Staub, I.; Donath, L. (European Journal of Sport Science, 2023)
Peak oxygen uptake (VO2peak) and speed at first (LT1, minimal lactate equivalent) and second lactate threshold (LT2 = LT1 +1.5 mmol·L-1) are crucial swimming performance surrogates. The present randomized controlled study investigated the effects of blood flow restriction (BFR) during low-intensity swimming (LiT) on VO2peak, LT1, and LT2. Eighteen male swimmers (22.7 ±3.0 yrs; 69.9 ±8.5 kg; 1.8 ±0.1 m) were either assigned to the BFR or control (noBFR) group. While BFR was applied during LiT, noBFR completed the identical LIT without BFR application. BFR of the upper limb was applied via customized pneumatic cuffs (75% of occlusion pressure: 135 ±10 mmHg; 8 cm cuff width). BFR training took place three times a week over 5 weeks (accumulated weekly net BFR training: 60 min·week-1; occlusion per session: 2-times 10 min·session-1) and was used exclusively at low intensities. VO2peak, LT1, and LT2 diagnostics were employed. Bayesian credible intervals revealed notable VO2peak improvements by +0.29 L·min-1 kg-1 (95% credible interval: -0.26 to +0.85 L·min-1 kg-1) when comparing BFR vs. noBFR. Speed at LT1 -0.01 m·s-1 (-0.04 to +0.02 m·s-1) and LT2 -0.01 m·s-1 (-0.03 to +0.02 m·s-1) did not change meaningfully when BFR was employed. Fifteen sessions of LIT swimming (macrocycle of 5 h over 5 weeks) with a weekly volume of 60 min with BFR application adds additional impact on VO2peak improvement compared to noBFR LIT swimming. Occasional BFR applications should be considered as a promising means to improve relevant performance surrogates in trained swimmers.